ANALISIS SURVIVAL MENGGUNAKAN REGRESI WEIBULL PADA LAJU KESEMBUHAN PASIEN TUBERKULOSIS PARU DI RSUD ALOEI SABOE KOTA GORONTALO - Isran K Hasan; Winni A. Pakaya; Novianita Achmad; Dewi Rahmawaty Isa (Universitas Negeri Gorontalo, 2021)
This study was aimed at discussing survival analysis in Pulmonary Tuberculosis patients in Aloei Saboe using Weibull regression to find out the factors that influence the patient’s recovery rate. To analyze the survival time, the Kaplan-Meier curve is used then the process continues into Log-Rank Test to see the differences between groups in a curve. Weibull Regression is used to determine the significant factors based on a log-rank test in the rate of recovery of Pulmonary Tuberculosis patients. The results of the study concluded age, shortness of breath, fever, cough, history of illness and smoking habits are factors that significantly influence the rate of recovery of Pulmonary Tuberculosis patients.